Evaluations on Colchian Amphorae retrieved from Fatsa/Cıngırt Kayası Excavations - Erol, Ayşe F.; Tamer, Deniz (Rei Cretariae Romanae Fautorum Acta, 2022)
This study aims to present Colchian amphorae samples that were obtained during excavations conducted in Cıngırt Kayası Fatsa/Ordu. The amphorae fragments retrieved from the excavations are dated from Hellenistic up to the Early Byzantine Period. Colchian products constitute the primary group among these amphorae from that time frame. The Colchian amphorae samples from the excavations have been evaluated in terms of their possible production centers due to their fabric, morphology and periodisation with parallel materials. These are the first samples of their kind from the southeastern part of Black Sea region. Some publications already talk about the possible presence of these amphorae in Southern Black Sea settlements. Indeed this possibility has been substantiated by the Colchian amphorae samples found at Cıngırt Kayası. They also present evidence to a trade relationship between Turkey’s northeastern coast and Colchis.